2005
DOI: 10.1074/jbc.m505818200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α (TNFα) Induces the Unfolded Protein Response (UPR) in a Reactive Oxygen Species (ROS)-dependent Fashion, and the UPR Counteracts ROS Accumulation by TNFα

Abstract: Accumulation of unfolded proteins in the endoplasmic reticulum (ER) causes ER overload, resulting in ER stress. To cope with ER stress, mammalian cells trigger a specific response known as the unfolded protein response (UPR). Although recent studies have indicated cross-talk between ER stress and oxidative stress, the mechanistic link is not fully understood. By using murine fibrosarcoma L929 cells, in which tumor necrosis factor (TNF) ␣ induces accumulation of reactive oxygen species (ROS) and cell death, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
301
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(325 citation statements)
references
References 31 publications
22
301
1
1
Order By: Relevance
“…There is increasing evidence that ER stress and inflammation are interconnected by the increased production of ROS (Harding et al, 2003;Xue et al, 2005;Gorlach et al, 2006). Our results indicate that Thapsigargin-induced ER stress increased ROS levels that correlated with the kinetics of ADAM17 sheddase activity.…”
Section: Adam17 Is Regulated By the Unfolded Protein Response T Rzymssupporting
confidence: 59%
See 1 more Smart Citation
“…There is increasing evidence that ER stress and inflammation are interconnected by the increased production of ROS (Harding et al, 2003;Xue et al, 2005;Gorlach et al, 2006). Our results indicate that Thapsigargin-induced ER stress increased ROS levels that correlated with the kinetics of ADAM17 sheddase activity.…”
Section: Adam17 Is Regulated By the Unfolded Protein Response T Rzymssupporting
confidence: 59%
“…The involvement of the UPR may be of specific significance in this process. It has been reported that inflammatory cytokines, including TNFa (Xue et al, 2005), cause ER stress and therefore activate the UPR in various cancer cell lines. Thus, increased ADAM17 sheddase activity under ER stress may be a result of the negative feedback loop and an adaptive response desensitizing cells from stress-inducing stimulation.…”
Section: Adam17 Is Regulated By the Unfolded Protein Response T Rzymsmentioning
confidence: 99%
“…Remarkably, orally active chemical chaperones that stabilize protein conformation and improve ER folding capacity can alleviate ER stress and can function as potent antidiabetic agents, restoring glucose homeostasis in mouse models of type 2 diabetes 60 . The ER is also a major source of ROS and, consequently, oxidative stress 61,62 . Oxidative stress is emerging as a feature of obesity and an important factor in the development of insulin resistance, and is frequently associated with mitochondrial dysfunction [63][64][65] .…”
Section: Nature Reviews | Molecular Cell Biologymentioning
confidence: 99%
“…Activated CREBH has enhanced production of proinflammatory mediators and also other transcription factors of the ER stress pathway can be participated in proinflammatory cytokine production such as XBP-1 and CHOP [48][49][50]. Proinflammatory cytokines, exclusively TNFα, can elevate ER stress and this event can cause a positive feedback mechanism that HLA-B27 misfolding lead to induce ER stress and proinflammatory cytokine production [51,52]. That feedback mechanism can contribute to understand the link between ER stress and a proinflammatory cytokine environment, also characteristic feature of AS patients.…”
Section: Hla-b27 Misfolding and Biochemical Propertiesmentioning
confidence: 99%